2002
DOI: 10.1034/j.1600-0536.2002.460404.x
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring levels of preservative sensitivity in Europe

Abstract: A 10-year multicentre analysis of the frequency of sensitivity to common preservatives collected in 16 centres in 11 countries has shown stable but persisting high levels of sensitivity to formaldehyde and 5-chloro-2-methyl-4-isothiazolin-3-one + 2-methyl-4-isothiazolin-3-one (MCI/MI). It has also revealed a significant increase in the level of reactivity to methyldibromoglutaronitrile (MDBGN) from 0.7% in 1991 to 3.5% in 2000. The current high level of sensitivity to MDBGN requires an urgent safety re-evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
178
2
7

Year Published

2004
2004
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(196 citation statements)
references
References 22 publications
9
178
2
7
Order By: Relevance
“…Sensitization potential of parabens is relatively low, when considering long-term application. During 1999-2000 in 11 European countries, the frequency of sensitization was 0.5% [22], during [2004][2005] in Great Britain among 6,958 patients; sensitization was 0.8% [23]. Among our patients with periorbital dermatitis, sensitization was 0.6%, however with no clinical relevance (none of the patients had used any ophtalmic product containing parabens).…”
Section: Discussionmentioning
confidence: 91%
“…Sensitization potential of parabens is relatively low, when considering long-term application. During 1999-2000 in 11 European countries, the frequency of sensitization was 0.5% [22], during [2004][2005] in Great Britain among 6,958 patients; sensitization was 0.8% [23]. Among our patients with periorbital dermatitis, sensitization was 0.6%, however with no clinical relevance (none of the patients had used any ophtalmic product containing parabens).…”
Section: Discussionmentioning
confidence: 91%
“…La MCI y la MI, al igual que otros conservantes del grupo formaldehído o mercuriales, pueden tener alto poder de sensibilización, como se ha demostrado por estudios experimentales y por la practica clínica, presentando la MCI mayor poder sensibilizante que la MI 12 . Actualmente constituye una de las causas más frecuente de alergia de contacto por preservativos [14][15][16] . Asimismo, además de la MCI y MI existen otras isotiazolinas disponibles para la producción de productos industriales, en particular, la benzisotiazolinona, que se utiliza con frecuencia en la pintura, pudiendo ser responsable de reacciones cruzadas con MCI/MI 17 .…”
Section: Discussionunclassified
“…While the overall prevalence of preservative contact allergy remains frequent in many EU member states, two Danish studies have shown that the overall prevalence and burden of preservative contact allergy is increasing every time a new preservative is marketed [6][7][8][9]. This has clearly been exemplified by the introduction of MI into the European cosmetic market in 2005 where MI was given a positive opinion by the SCCS and entered onto Annex V as a preservative allowed for use in cosmetic products.…”
Section: Temporal Trend Of Contact Allergy To Preservativesmentioning
confidence: 99%
“…Notwithstanding recent epidemics of contact allergy to single (troublesome) preservatives, the overall prevalence of contact allergy is maintained at alarmingly high levels above 10% in consecutive patch-tested dermatitis patients [6][7][8][9]. The former comprehensive observational study by Wilkinson et al showed that in 80,000 European patients from 11 European centers, stable and high levels of contact allergy to the "old and prior epidemic" preservatives (formaldehyde, formaldehyde releasers and MCI/MI) were observed [9].…”
Section: Temporal Trend Of Contact Allergy To Preservativesmentioning
confidence: 99%
See 1 more Smart Citation